An S-alkyl thiocarbamate-based biosensor for highly sensitive and selective detection of hypochlorous acid. Issue 18 (14th August 2018) - Sun, Jian; Feng, Fude
Abstract : An S -alkyl thiocarbamate bond in a caged fluorophore is selective to target hypochlorous acid but stable against Hg 2+ . Abstract : We reported a near-infrared biosensor that features a dihydromethylene blue and an S -alkyl thiocarbamate linker to detect hypochlorous acid in a drastic fluorescence turn-on response. We achieved high sensitivity at the nanomolar level and high selectivity that resolves the interference issue with mercury ions and other transition metal ions. We demonstrated the response mechanism by analysing the released segments, and investigated the imaging capability to detect both exogenous and endogenous hypochlorous acid in living cells.